Understanding Influence of Social Media Marketing of Masstige Fashion Brands on Generation Z Female Indian Consumers - Singh, Balgopal; Dagur, Arti (Indian Journal of Marketing, 2022)
Social media has improved marketers’ connectivity with consumers. Targeting the Generation Z population through social media can provide ample opportunity for selling brands. This study aimed to examine the influence of social media marketing on the purchase intention of affordable luxury fashion brands among Generation Z female Indian consumers. Based on the uses and gratification theory, branding theory, and conspicuous consumption theory, a conceptual model was developed to explore the effect of social media marketing on brand equity and purchase intention and analyze the mediating role of brand equity on the relationship between social media marketing and purchase intention. Primary data were collected through a structured questionnaire from 348 female university students selected using convenience purposive sampling with the condition of using social media and following luxury fashion brand pages. Covariance-based structural equation modeling and path analysis was used to test the proposed hypotheses. The results showed that social media marketing significantly influenced brand equity and purchase intention, and brand equity partially mediated the relationship between social media marketing and purchase intention. The findings indicated that social media marketing of affordable luxury fashion brands raised both feeling and action. This study added valuable insights to the masstige theory and marketing of masstige brands.